The Relationship Between Decision Making and Leadership Responsibility in The Campus Environment - Gracia Christoyanne Situmorang (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
Leadership in the campus environment plays an important role in shaping organizational culture and supporting the development of students as future leaders. One of the competencies required in leadership is the ability to make decisions effectively, which must go hand in hand with a sense of moral and social responsibility. This study aims to analyze the relationship between decision- making skills and leadership responsibility in the context of campus organizations. This study uses the Systematic Literature Review method by examining various scientific publications that discuss decision making, leadership ethics, member participation, and student leader accountability. The results of the study indicate that decisions based on ethical considerations, rational analysis, and the involvement of organizational members tend to result in higher leadership responsibility. In addition, leaders who involve members in the decision- making process are able to build organizational trust and improve the effectiveness of internal communication. These findings confirm that wise decision-making is a key factor in shaping campus leaders who are integrity, transparent, and capable of creating a collaborative organizational environment. This research contributes to the development of literature on student leadership by highlighting the importance of integrating decision-making processes and leadership responsibility in supporting the achievement of organizational goals.